Relationship Between Social Conflicts and Chronic Illnesses in Kabale Municipality. - Aharimpisya, Dreck (Kabale University, 2024)
This study focused on the relationship between social conflicts and chronic illness in Kabale Municipality. Social conflicts and chronic illness are major issues affecting individuals and communities globally. Understanding the connection between these issues is essential for addressing health disparities and challenges in different communities. In Europe, social conflicts have been associated with inequalities in healthcare access and quality, resulting in negative health outcomes for marginalized groups. Historically, social conflicts have impacted various aspects of society, including health, and are often driven by factors like socioeconomic inequality, discrimination, and political instability (Blosnich et al., 2017). This section also examines the prevalence of chronic illnesses in Kabale Municipality and potential strategies for improving healthcare delivery for those with chronic conditions amid social conflicts. Further research in these areas can provide stakeholders with a deeper understanding of the complex effects of chronic illnesses on learning outcomes and inform interventions designed to support affected students in Kabale Municipality.